Analysis of the Anatomic Relationship Between the Mandibular First Molar Roots and Mandibular Canal Using Cone-Beam Computed-Tomography in 101 Dogs - Berning, Jamie A.; Snyder, Christopher J.; Hetzel, Scott; Sarment, David P. (Frontiers in Veterinary Science, 2020)
The mandibular first molar (M1) tooth of the dog is commonly involved in dental procedures. Tooth roots and the mandibular canal can vary in location, which has not been described on a large scale. The objective of this study was to describe the three-dimensional anatomic relationship of the mandibular M1 tooth roots and the mandibular canal in dogs. Cone-beam computed tomography (CBCT) was used to evaluate the anatomic relationship between the M1 tooth roots and the mandibular canal. CBCT images were collected from 101 canine cadaver heads from a variety of unknown breeds. All skulls used in this study were mesaticephalic, confirmed by facial index calculations. The position of the apex in relation to the mandibular canal and in relation to the buccal and lingual cortices was recorded and analyzed in relation to mandibular bone height: root length ratio. When evaluating the apex in a buccal-lingual relationship, the tooth roots were found to be located closer to the lingual cortex in 73.3% of M1 roots. Tooth root apical positions were found to be symmetric between the right and left side of the mouth in 93% of mesial roots and 95% of distal roots. Apical positions relative to the mandibular canal within the same tooth were found to be consistent in 52% of teeth. Teeth with roots dorsal to the mandibular canal were associated with the largest mandibular bone height: root length ratio. CBCT provides a more precise overview than dental radiographs of three-dimensional anatomy. The tooth root position can be estimated in a clinical setting based on the ratio of mandibular bone height to tooth root length obtained from intraoral radiographs. Understanding the relative location of important anatomic structures is key to avoiding complications associated with various dental procedures. This study has documented that assessing anatomic structures with 2D imaging alone is flawed, and the large majority of dogs have M1 roots closer to the lingual aspect than the buccal aspect of the mandible.